1997
DOI: 10.2355/isijinternational.37.1112
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Control of Initial Solidification in Continuous Casting of Steel by Low Frequency Alternating Magnetic Field.

Abstract: A markedimprovement of the surface quality of casts and a break-through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Recently, the casting experiments showed that the quality of the billet surface became much better with SC-EMCC technology than with conventional continuous casting technology. [2][3][4] However, one of the key factors is the mold design for applying this SC-EMCC technology in steelmaking. The mold used in the SC-EMCC should achieve high magnetic penetrability and suitable cooling ability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the casting experiments showed that the quality of the billet surface became much better with SC-EMCC technology than with conventional continuous casting technology. [2][3][4] However, one of the key factors is the mold design for applying this SC-EMCC technology in steelmaking. The mold used in the SC-EMCC should achieve high magnetic penetrability and suitable cooling ability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known from laboratory experiments that the surface quality of cast steel is much improved by EMC. [3][4][5][6] And the magnetic frequency adopted in EMC ranges to wide area, from few hundreds hertz to several ten kilo-hertz. The authors have already confirmed the beneficial effects on the surface quality of cast billet using high frequency magnetic field of 20 kHz, 4) in the viewpoint of stabilization of meniscus which is greatly influenced by the ratio of magnetic skin depth to the characteristic length of the billet.…”
Section: Introductionmentioning
confidence: 99%
“…Although the electromagnetic force was calculated, but the deep analysis about it was not carried out. Application of low frequency electromagnetic field was researched in literature, 2) the frequency is aimed at 60 Hz. In literature, 3) the authors researched the effect of intermittent high frequency magnetic field on initial solidification, the frequency is fixed on 20 kHz.…”
Section: Introductionmentioning
confidence: 99%